Conducting polymers: a comprehensive review on recent advances in synthesis, properties and applications - K, Namsheer; Rout, Chandra Sekhar (RSC advances, 2021)
Conducting polymers are extensively studied due to their outstanding properties, including tunable electrical property, optical and high mechanical properties, easy synthesis and effortless fabrication and high environmental stability over conventional inorganic materials. Although conducting polymers have a lot of limitations in their pristine form, hybridization with other materials overcomes these limitations. The synergetic effects of conducting polymer composites give them wide applications in electrical, electronics and optoelectronic fields. An in-depth analysis of composites of conducting polymers with carbonaceous materials, metal oxides, transition metals and transition metal dichalcogenides etc. is used to study them effectively. Here in this review we seek to describe the transport models which help to explain the conduction mechanism, relevant synthesis approaches, and physical properties, including electrical, optical and mechanical properties. Recent developments in their applications in the fields of energy storage, photocatalysis, anti-corrosion coatings, biomedical applications and sensing applications are also explained. Structural properties play an important role in the performance of the composites. Conducting polymers are extensively studied due to their outstanding properties, including tunable electrical property, optical and high mechanical properties, easy synthesis and effortless fabrication and high environmental stability over conventional inorganic materials.